PENGARUH MODEL PEMBELAJARAN COMPUTER SUPPORTED COLLABORATIVE LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 6 PALEMBANG - Eliza Eliza; M. Djahir Basir; Ikbal Barlian (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This study aimed to know the difference of the effect between Computer Supported Collaborative Learning model and Computer Based Learning model toward Economy student learning outcomes in SMA 6 Palembang. This study used True Experimental Design, with Pretest-Postest Control Group Design. Population of this study were all of the IIS tenth grade students in SMA 6 Palembang that consist of 4 classes odd semester 2014-2015 amounted 105 students. The sample of this study was taken by using Cluster Random Sampling technique and it concluded X IIS 2 as an experimental class with 26 students. Technique of collecting data used test and observation. The statistics used to analyze data was parametric statistics with hypotheses (t-test) by using the formula of related t-test. The result of t-test is tcount 3,416 and tinterpolation 2,009. Thus, the hypotheses in this study is true that there is difference of the effect between Computer Supported Collaborative Learning model and Computer Based Learning model toward Economy student learning outcomes in SMA 6 Palembang. The difference can be seen from the student learning outcomes in the experimental class with average score of pretest 56,66 and posttest 86,66 while in the controlled class with average score of pretest 53,30 and posttest 80. It shows the difference in the effect of Computer Supported Collaborative Learning model in the experimental class and the controlled class which was given Computer Based Learning model